SAN Volume Controller Best Practices and Performance Guidelines - Tate, Jon; George, Deon; Hoss, Thorsten; Hruby, Ronda; MacQuarrie, Ian; Mellish, Barry; Mescher, Peter (IBM Redbooks, 2008)
This IBM® Redbook captures some of the best practices based on field experience and details the performance gains that can be achieved by implementing the IBM System Storage™ SAN Volume Controller. This book is intended for very experienced storage, SAN, and SVC administrators and technicians. Readers are expected to have an advanced knowledge of the SVC and SAN environment, and we recommend these books as background reading: IBM System Storage SAN Volume Controller, SG24-6423 Introduction to Storage Area Networks, SG24-5470 Using the SVC for Business Continuity, SG24-7371.
Keywords: Storage area networks (Computer networks); Electronic data processing -- Backup processing alternatives; Virtual storage (Computer science); Réseaux de stockage (Informatique); Sauvegarde (Informatique); Ordinateurs; Mémoires virtuelles; Electronic data processing; Backup processing alternatives